«Seguìta però a dovere». Considerazioni sulla riflessione politica leopardiana oltre i due concetti di natura - Baggi, Paolo Giovanni (Rivista Internazionale di Studi Leopardiani, 2025)
Leopardi’s reflections on politics and society revolve around a vision of nature that remains beneficial, even in the face of the discovery of evil within the natural order. Rather than undermining this view, the specific form of materialism Leopardi develops provides the most appropriate theoretical framework for understanding how illusion operates as a mechanism of control over the social order, preventing its contradictions from erupting.